Semantic wiki-based ontology evolution - Kasisopha, Natsuda; Wongthongtham, Pornpit (IEEE, 2009)
Ontology plays a vital role in sharing conceptualizations and terminology interpretable by machines. There are many tools that provide features for Ontology evolution and Ontology maintenance but those tools have limitation on the social involvement perspectives. As results, only a group of Ontology Engineers point of views has on the Ontology concepts. Thus Semantic Wiki allows people to get involve in maintaining and evolving the Ontology. Semantic wiki has characteristic of Usability, Timeliness, Interoperability, Reuse of Knowledge, Formalization and Express ability. It also supportsthe knowledge models that represent in Resource Description Framework (RDF) schema and Web Ontology Language (OWL).